Analisis Perbandingan Kinerja Keuangan Perusahaan dan Nilai Perusahaan Antara Pra Tax Amnesty dengan Pasca Tax Amnesty di Indonesia - Nila Gemala; Aries Tanno; Rahmat Kurniawan (Universitas Batanghari Jambi, 2022)
Tax amnesty has an impact on economic growth that can have an impact on financial performance and company value. This study was conducted to empirically test the differences in company financial performance and firm value between the pre-tax amnesty and post-tax amnesty periods. The companies used as samples are 178 companies that participate in the tax amnesty listed on the IDX. The period used is 2013-2015 for pre-tax amnesty and 2016-2018 for post-tax amnesty. Hypothesis testing using SPSS version 26 with ANCOVA analysis. The results of the study prove: 1) The company's financial performance does not have a significant difference between pre-tax amnesty and post-tax amnesty from the leverage ratio, liquidity ratio, and activity ratio, while the profitability ratio has a significant difference and experienced a decline in the company's financial performance in the post-tax amnesty. 2) Firm value has a significant difference between pre-tax amnesty and post-tax amnesty and has decreased firm value in post-tax amnesty 3) Firm size has a relationship with CR, DER, and Tobins-Q in seeing the effect of firm performance and firm value on tax amnesty, 4) Industry type has a relationship with CR, TATO, and Tobins-Q in seeing the effect of company performance and company value on tax amnesty.